PENGATURAN PENGGANTIAN BIAYA AHLI DALAM MEMBERIKAN KETERANGAN DI PERSIDANGAN BERDASARKAN HUKUM ACARA PIDANA INDONESIA - Resti Nauli Halim. B; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Indonesia is a state based on law (rechtstaat), where one of the existing arrangements in Indonesia is the code of Criminal Procedure (Criminal Procedure Code) as codification and univfikasi law. Under the provisions of Article 184 paragraph (1) of the law on Criminal Proceedings (Criminal Procedure Code) provides that in criminal proceedings, there is valid evidence, namely: witness testimony, expert testimony, letters, instructions and testimony of the defendant. Evidence from expert testimonies have an important role in making light of a criminal case in finding the material truth. In article 229 paragraph (1) Criminal Procedure Code mentioned the right to a replacement cost of a witness or expert who summons to appear in court, but in practice it is not uncommon these rights are ignored and not optimal to run. The purpose of this thesis are: first, to know the idea of reimbursement expert testified at the trial by the Criminal Procedure Code Indonesia. Second, to determine the mechanism of submission of an expert witness in criminal justice according to the Criminal Procedure Law of Indonesia.This research is a normative juridical or normative legal research. The data source is secondary data consisting of primary legal materials, secondary law and tertiary legal materials. Data collection techniques in this study is a review of literature and documentary studies and data analysis used teknik ie deduktive method.From the results of research can be concluded, first implementation of the right to a replacement cost for the expert still are not running optimally according to Article 229 of the Code of Criminal Procedure (Criminal Procedure Code). Second, under of Article 180 paragraph (1) of the Law on Criminal Proceedings (Criminal Procedure Code) provides that the presiding judge may request expert session. If the presiding judge or court hearing the request for information is not expert each party as well as the prosecution alleged, then it can guarantee the impatiality of experts in ensuring the rights of the accused and the prosecution are common cosam judges in finding the material truth. Advice writer, first, to reinforce the responsibility of the state to compensate the experts were called in any court process as outlined in the Code of Criminal Procedure (Criminal Procedure Code). The second, more detailed evidence on when the expert testimony may be required in order to guarantee the rights of each institution to call an expert without ignoring the rights of suspects and defendants.Keywords: Replacement Cost – Expert – In Trial